The quantification of root exudation by an in-situ method based on root morphology over three incubation periods - Zhang, Chengfu; Cai, Yinmei; Zhao, Qingxia; He, Tengbing; Mao, Tianxu; Zhang, Tao; Zhang, Limin; Su, Weici (Frontiers in Plant Science, 2024)
Investigating the quantity and spatiotemporal dynamics of metabolite release from plant roots is essential if we are to understand the ecological significance of root exudates in the rhizosphere; however, this is difficult to quantify. In the present study, we quantified in situ root exudation rates during three incubation periods (0-24, 24-48, and 48-72 h) and fine roots within four diameter ranges (<0.8, 0.8-1.0, 1.0-1.2, and 1.2-2.0 mm), and also measured nine morphological traits in the fine roots of Pinus massoniana.Higher root carbon (C) exudation rates were detected during the 0-24 h period. During the 0-24 h and 24-48 h periods, N uptake rates were higher than N exudation rates, while during the 48-72 h period, N exudation rates exceeded uptake rates. As C exudation increased during 0-48h incubation period, the uptake of N tended to level out. The exudation of C from the roots was positively associated with root mass, length, surface area, volume, the number of root tips, and the root tissue density, when incubated for 0-24 h and 24-48 h. Furthermore, length-specific C exudation rates, along with N exudation and uptake rates, all increased as the diameter of the fine roots increased. We concluded that the 24-48 h incubation period was the most suitable for capturing root exudates from P. massoniana. The release of root exudates could be efficiently predicted by the fine root morphological traits, although the accuracy of prediction depended on the incubation period. Higher values for fine root morphological traits were generally indicative of higher nutrient requirements and tissue investment, as well as higher C exudation rates.